Social Identity Strategies in Recent Economics - John B. Davis (Tinbergen Institute, 2005)
This paper reviews three distinct strategies in recent economics for using the concept of social identity in the explanation of individual behavior: Akerlof and Kranton's neoclassical approach, Sen's commitment approach, and Kirman et al.'s complexity approach. The primary focus is the multiple selves problem and the difficulties associated with failing to explain social identity and personal identity together. The argument of the paper is that too narrow a scope for reflexivity in individual decision-making renders the problem intractable, but that enlarging this scope makes it possible to explain personal and social identity together in connection with an individual behavior termed comparative value-objective evaluation. The paper concludes with recommendations for treating the individual objective function as a production function.
Keywords: D01; D63; Z13; 330; identity; personal identity; reflexivity; individual objective function; Wohlfahrtstheorie; Soziale Norm; Normative Ökonomik